First documentation of long-distance travel by a Florida manatee to the Mexican Caribbean. Issue 5 (3rd September 2022) - Castelblanco-Martínez, Delma N.; Alvarez-Alemán, Anmari; Torres, Raúl; Teague, Amy L.; Barton, Sheri L.; Rood, Kari A.; Ramos, Eric A.; Mignucci-Giannoni, Antonio A.
Abstract : West Indian manatees ( Trichechus manatus ) are separated into two allopatric subspecies: the Florida manatee ( T. m. latirostris ) and the Antillean manatee ( T. m. manatus ). In the winter of 2020–2021, an adult manatee was sighted off the coast of Cancun, Quintana Roo, Mexico, in areas where Antillean manatees are not typically seen. The individual had distinct watercraft scars on its body, which were matched using photo-identification to a known male Florida manatee (PE424) that had been repeatedly photographed in Florida since 1998. This is the first record of a Florida manatee visiting the Mexican Caribbean. Previous reports of individuals from this subspecies in Cuba, combined with genetic evidence, suggest some level of connectivity among geographically separated manatee populations. Highlights: We present the first evidence of a long-distance movement by a manatee from Florida to the Yucatan Peninsula (Quintana Roo, Mexican Caribbean). This case, previous reports of Florida manatees in Cuba, and genetic evidence, suggest a certain degree of genetic mixture among the two subspecies.